The Effect of Using the Savi Model Toward Reading Comprehension Across Cognitive Style - Muhammad Riko Yohansyah Zulfahmi; Melyann Melani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aimed to identify the effect of cognitive styles (that is, field-dependent and field-independent) on reading comprehension using the SAVI model (somatic, auditory, visual, and intellectual). The 52 students from two classes participated in the study, assigned to experimental and control classes. The experimental class was treated by teaching the SAVI model and the control group was taught conventionally (Teacher Centre). Students in the control and experimental classes were divided into groups based on their cognitive style (dependent versus independent) results on the GEFT (Group Embedded Figure Test). The results of the study indicated that it was about the interaction between cognitive style and reading comprehension. Research results show that there are differences in student reading performance between students using the SAVI learning model and the direct learning model (Teacher Center). There is an important interplay between learning models and students' cognitive styles regarding their ability to comprehend what they read. Among students with subject-independent cognitive styles, those who received the SAVI learning model performed better in reading than those who received the direct learning model. Students in the direct learning model with subject-dependent cognitive styles and reading comprehension perform better than those in the SAVI learning model.